PURA DALEM TUNON DADYA SEMALUNG DI DESA ABABI KECAMATAN ABANG KABUPATEN KARANGASEM PERSFEKTIF SEJARAH, RELIGIUSITAS DAN FUNGSI - I Ketut Wiriawan (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
In Dadya Semalung, Ababi Village, Abang Subdistrict, Karangasem Regency, there is a temple, Pura Dalem Tunon, which was thrown by Dadya Semalung manners. The study was conducted on the basis of researchers' interest in relation to the existence of Pura Dalem, which was issued by Krama Dadya (a citizen who was gathered in a community group or group). In addition to this, the importance of the history of the temple as well as the religiosity of the community and the function of the temple is also a concern by researchers so that researchers feel interested in analyzing the study of the history of the existence of the Dalem Tunon Dadya Semalung Temple in Ababi Village, Abang District, Karangasem Regency, the Structure of the Dalem Tunon Dadya Semalung Temple in the Village Ababi Abang District Karangasem Regency, and the function of Pura Dalem Tunon Dadya Semalung in Ababi Village Abang District Karangasem Regency. Pura Dalem Tunon was founded around 600 years ago, which is the width (death) of Jero Dukuh Sakti which is the first Sulinggih from Arya Gajah Para descent in the village of Pakraman Ababi. The structure of Dalem Tunon Dadya Semalung Temple consists of 3 parts in accordance with the Tri Mandala concept with 10 buildings or palinggih. The function of Pura Dalem Tunon Dadya Semalung has a religious function that is as a vehicle for purification or samshara, and a function of togetherness.Keywords : History of Dalem Tunon Dadya Semalung Temple, religiosity and function